Strategi Peningkatan Pendapatan Asli Daerah Melalui Sektor Pajak Bumi Dan Bangunan Perkotaan Dan Perdesaan (Studi Kasus Badan Pendapatan Daerah Kota Bengkulu) - Purnawan, Heru; Deswanti, Futri Rahayu; Mulyadi, Mulyadi; Aprianty, Henny (Jurnal Publisitas, 2024)
Land and Building Tax (PBB) is one type of government tax that is collected mainly on land and buildings. According to the Land and Building Tax Law Number 12 of 1985, it is permissible to build buildings on designated land. This study uses a qualitative approach with a descriptive method. The results of the study found that PBB has not been maximized because the accuracy of the Land and Building data is still not in accordance with the reality of community asset ownership where there are differences in purchase price, size, and several other data. In addition, low purchasing power in Bengkulu City makes some assets that are not used as a business make people reluctant to comply with PBB payments. Moreover, in this strategy effort, it is a challenge because many Civil Servants / State Civil Apparatus still do not make mandatory PBB payments for their ownership. From the results of the study and findings in the field, it can be concluded that the strategy of the Bengkulu City Regional Revenue Agency in increasing land and building taxes in rural and urban areas in 2023 has not been running well so that improvements still need to be made. The strategies implemented include a direct approach to the community directly, socialization to taxpayers, and visiting houses one by one.